III-Nitride-Based Quantum Dots and Their Optoelectronic Applications - Weng, G. E.; Ling, A. K.; Lv, X. Q.; Zhang, J. Y.; Zhang, B. P. (Nano-Micro Letters, 2011)
During the last two decades, III-nitride-based quantum dots (QDs) have attracted great attentions for optoelectronic applications due to their unique electronic properties. In this paper, we first present an overview on the techniques of fabrication for III-nitride-based QDs. Then various optoelectronic devices such as QD lasers, QD light-emitting diodes (LEDs), QD infrared photodetectors (QDIPs) and QD intermediate band (QDIB) solar cells (SCs) are discussed. Finally, we focus on the future research directions and how the challenges can be overcome.